Teori Kognitif dan Implikasinya Dalam Proses Pembelajaran Individu - Eran Wandani; Neng Shufi Sufhia; Neni Eliawati; Imas Masitoh (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Each individual has the ability to develop his own knowledge. This means that the knowledge possessed by each individual can be formed independently through continuous and ever-changing interactions with the surrounding environment. When interacting with the environment, individuals are able to adapt and organize their environment, resulting in changes in their cognitive structure. As a result, knowledge, insight, and understanding are growing. Individuals are also able to modify the experience gained through the environment, resulting in new knowledge or new findings.Therefore, education is not only about transferring knowledge, but also about stimulating individual cognitive structures to be able to produce new knowledge and findings. In addition, individualization in learning is also very important. This means that in the learning process, the treatment of individuals must be based on their cognitive development.